Comparative analysis of characterization techniques of GQDs-based photovoltaic applications: A review - Rabeya R.; Mahalingam S.; Manap A.; Satgunam M.; Akhtaruzzaman M.; Hua C.C. (Elsevier GmbH, 2023)
Graphene; Semiconductor quantum dots; Solar cells; 'current; Analyse; Characterization; Characterization techniques; Comparative analyzes; Optical characterization; Performance; Photoelectrode; Photovoltaic applications; Photovoltaics; Morphology